2006
DOI: 10.1038/sj.eye.6702350
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness and visual field damage in glaucoma patients

Abstract: Purpose To verify whether there was a significant correlation between central corneal thickness (CCT) and visual field damage in patients with primary open angle glaucoma (POAG). Methods A total of 99 eyes with POAG were consecutively recruited. Patients were classified as glaucomatous based on visual field and optic nerve head damage. All underwent applanation tonometry, Humphrey perimetry, and measurement of CCT with ultrasonic pachymetry. Based on CCT value, the sample was split at the mode in two groups (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Thinner central cornea with GAT IOP measurement: Strong evidence exists for thinner central cornea as a risk factor for progression from ocular hypertension to POAG, but evidence is mixed for thinner central cornea as a risk factor for progression in glaucoma. 81,88,91,[233][234][235]237,526,549,550 Decreased corneal hysteresis: Corneal hysteresis is a measure of the viscoelastic dampening of the cornea and has been shown to be associated with the risk of glaucoma progression. [90][91][92][93] Lower ocular perfusion pressure 58,100 Pseudoexfoliation 51,58,551 Poor adherence with medications [552][553][554] Damage in one eye is associated with an increased risk of future damage in the other eye.…”
Section: Risk Factors For Progressionmentioning
confidence: 99%
“…Thinner central cornea with GAT IOP measurement: Strong evidence exists for thinner central cornea as a risk factor for progression from ocular hypertension to POAG, but evidence is mixed for thinner central cornea as a risk factor for progression in glaucoma. 81,88,91,[233][234][235]237,526,549,550 Decreased corneal hysteresis: Corneal hysteresis is a measure of the viscoelastic dampening of the cornea and has been shown to be associated with the risk of glaucoma progression. [90][91][92][93] Lower ocular perfusion pressure 58,100 Pseudoexfoliation 51,58,551 Poor adherence with medications [552][553][554] Damage in one eye is associated with an increased risk of future damage in the other eye.…”
Section: Risk Factors For Progressionmentioning
confidence: 99%
“…It is important to address two main factors that could explain the relationship between corneal parameters and ONH morphology (at diagnosis) in glaucomatous eyes. First, as lower CCT values cause an underestimation of the true IOP, there may be a delay in the diagnosis of POAG which would likely influence the disease stage (and consequently influence the ONH morphology) at diagnosis 46 . Second, it has been speculated that the biomechanical characteristics of the cornea may reflect the biomechanical characteristics of the ONH complex 11,38,39,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The influence of central corneal thickness (CCT) on IOP values measured with GAT has been demonstrated (Ehlers et al 1975;Whitacre et al 1993;Wolfs et al 1997) and is now taken into account in the interpretation of IOP measurements. Several studies have already shown a significant correlation between a thin CCT and the severity of glaucomatous neuropathy (Herndon et al 2004;Jonas et al 2005;Congdon et al 2006;Kniestedt et al 2006;Papadia et al 2007 Study (OHTS), a thin CCT may be an independent risk factor for the development and progression of glaucoma in patients with OHT (Gordon et al 2002).…”
Section: Introductionmentioning
confidence: 99%